Identification of natural phytochemicals as AKT2 inhibitors using molecular docking and dynamics simulations as potential cancer therapeutics - Jibon Kumar Paul; Mahir Azmal; Md Naimul Haque Shohan; Mohua Mrinmoy; ANM Shah Newaz Been Haque; Omar Faruk Talukder; Ajit Ghosh (Heliyon)
The PI3K/AKT/mTOR pathway is central in regulating key cellular processes such as proliferation, survival, metabolism, and angiogenesis. Dysregulation of this pathway, particularly in the AKT2 isoform, is commonly observed in cancers such as breast, ovarian, and pancreatic cancers, leading to enhanced tumor progression, metastasis, and therapeutic resistance. Therefore, targeting AKT2 for inhibition is a promising strategy for cancer therapy. This study utilized molecular docking and dynamics simulations to identify natural phytochemicals that inhibit AKT2. Molecular docking results revealed that millettone (CID 442810) exhibited the highest binding affinity to AKT2, with a docking score of −9.5 kcal/mol, followed by uzarigenin (CID 92760), dihydrobiochanin A (CID 439784), and abyssinone I (CID 442152) with docking scores of −9.0 kcal/mol, −8.9 kcal/mol, and −8.7 kcal/mol respectively, outperforming the control inhibitor, ipatasertib (CID 24788740) docking score of −7.56 kcal/mol. Molecular dynamics simulations indicated that millettone, uzarigenin, and dihydrobiochanin A demonstrated strong binding affinities and stable interactions with AKT2, suggesting their potential as therapeutic agents for cancers that involve AKT2 hyperactivation. Notably, uzarigenin's superior stability, as evidenced by its lower root mean square deviation (RMSD), which measures structural stability, and solvent-accessible surface area (SASA), which indicates molecular compactness, highlights its promise as a potent inhibitor of AKT2. Future in vitro and in vivo studies will be crucial to confirm the efficacy of these inhibitors in reducing tumor progression and their potential applications. Given that AKT2 also plays a role in neuronal survival and plasticity, these compounds may have potential applications in neurodegenerative diseases such as Alzheimer's, warranting further investigation into their dual therapeutic relevance.